Production process management training for the home industry of Baso Aci, Ngadiluwih, Kediri - Santoso, Heribertus Budi; Indrasari, Lolyka Dewi; Komari, Ana; Tripariyanto, Afiff Yudha; Rahayuningsih, Sri (Community Empowerment, 2021)
The production process of Baso Aci will have an influence on the taste, if the composition of the raw materials is not appropriate. The purpose of community service is to identify the process of producing Baso Aci 'Tata Snack' both from the raw materials and equipment used and determine the method to regulate the capacity of the composition of raw materials. The method used was lecture, discussion and Q&A. This activity resulted in the identification of the meatball production process "Tata Snack" both from the raw materials and equipment used. Baso Aci with a very simple production process require continuity. Its function is to maintain the taste and quality of Baso Aci. This activity can be further expanded by reviewing equipment updates to increase labor productivity.